Nicotinamide Phosphoribosyltransferase May Be Involved in Age-Related Brain Diseases - Liu, Li-Ying; Wang, Feng; Zhang, Xia-Yan; Huang, Peng; Lu, Yun-Bi; Wei, Er-Qing; Zhang, Wei-Ping (PLOS ONE, 2012)
Nicotinamide phosphoribosyltransferase (NAMPT) is a key enzyme for nicotinamide adenine dinucleotide (NAD) biosynthesis, and can be found either intracellularly (iNAMPT) or extracellularly (eNAMPT). Studies have shown that both iNAMPT and eNAMPT are implicated in aging and age-related diseases/disorders in the peripheral system. However, their functional roles in aged brain remain to be established. Here we showed that upon aging, NAMPT level increased in serum but decreased in brain, decreased in cortex and hippocampus but remained unchanged in cerebellum and striatum in brain, and increased in microglia but likely decreased in neuron. Accordingly, total NAD (tNAD) level significantly decreased in hippocampus, cerebellum and striatum in aged brain. Application of recombinant NAMPT, mimicking the elevated serum NAMPT level, enhanced the susceptibility of cerebral endothelial cells to ischemic injury, while inhibition of iNAMPT by FK866, a specific inhibitor, reduced intracellular NAD level and induced neuronal death. Taken together, we have revealed a region- and cell-specific change of NAMPT level in brain and serum upon aging, deduced its potential consequences, which suggests that NAMPT is a regulatory factor in aging and age-related brain diseases.